Antenatal mother–infant bonding scores are related to maternal reports of infant crying behaviour. (20th October 2017) - Kommers, Deedee R.; Truijens, Sophie E. M.; Oei, S. Guid; Bambang Oetomo, Sidarto; Pop, Victor J. M.
Abstract: Objective: To assess the relation between antenatal mother–infant bonding scores and maternal reports of infant crying behaviour. Background: Crying is normal behaviour and it is important for parent–infant bonding. Even though bonding starts antenatally, the relation between antenatal bonding scores and infant crying behaviour has never been studied. Method: A secondary analysis was performed on data that were gathered in a large prospective study within our region. Bonding was assessed using an antenatal bonding questionnaire at 32 weeks gestational age. The crying behaviour of infants was assessed with three questions at six weeks postpartum. Crying was termed excessive (EC+) when mothers perceived the crying to be 'every day', 'often' or 'very often', and with 'crying episodes lasting more than 30 minutes'; in other words, when mothers scored high on all three questions. The relation between bonding and crying was examined using a multiple logistic regression analysis, including adjustment for relevant variables, especially maternal depression as measured with the Edinburgh Depression Scale. Results: In total, 894 women were included of whom 47 reported EC+ infants (5.3%). Antenatal bonding scores were significantly related to the reporting of crying behaviour, even after adjustment for relevant variables ( p = 0.02). Each extra point on the bonding scale reduced the EC+ risk with 14% (OR = 0.86, 95% CI [0.76–0.97]). Conclusion: Mothers with lower antenatal bonding scores were more likely to report an EC+ infant. Future research should further explore the concept of antenatal bonding, its relation with EC and risks associated with EC.